Effect of Coronary Computed Tomography Angiography Disease Burden on the Incidence of Recurrent Chest Pain. (2nd July 2014) - Ahmadian, Homayoun R.; Thomas, Dustin M.; Shaw, David J.; Barnwell, Megan L.; Jones, Ronald L.; McDonough, Ryan J.; Prentice, Ryan L.; Lin, Charles K.; Slim, Ahmad M.
Abstract : Introduction. The purpose of this study is to investigate chest pain evaluations after initial coronary computed tomography angiography (CCTA) based upon coronary artery disease (CAD) burden. Methods. CCTA results of 1, 518 patients were grouped based on the CCTA results into no CAD, nonobstructive CAD (<50% maximal diameter stenosis), or obstructive CAD (≥50% stenosis). Chest pain evaluation after initial CCTA and rates of major adverse cardiovascular events (MACE) defined as the incidence of all-cause mortality, nonfatal MI, ischemic stroke, and late revascularization (>90 days following CCTA) were evaluated. Results. MACE rates were higher with obstructive CAD compared to nonobstructive CAD and no CAD (8.9% versus 0.7%, P < 0.001 ; 8.9 versus 1.6%, P < 0.001 ). One hundred seventy-four patients (11.5%) underwent evaluation for chest pain after index CCTA with rates significantly higher with obstructive CAD compared to both nonobstructive CAD and no CAD (7.5% versus 13.9% versus 17.8%, P < 0.001 ). The incidence of repeat testing was more frequent in patients with obstructive CAD (no CAD 36.5% versus nonobstructive CAD 54.9% versus obstructive CAD 67.7%, P = 0.015 ). Conclusion. Absence of obstructive disease on CCTA is associated with lower rates of subsequent evaluations for chest pain and repeat testing with low MACE event rates over a 22-month followup.